Historical views and viewpoints in Malaga until 1850. - Ruiz-Padrón, Luis; Gámiz-Gordo, Antonio (University of L’Aquila, 2019)
As a documentary source, this research uses an important and little-known legacy of views of the city of Malaga and its surroundings, from the 16th century until the arrival of photography in the mid-19th century. Its intention is to promote knowledge of the urban landscape, considering its transformations through its images. Therefore, several drawings by fifteen authors have been selected and analysed: Wyngaerde (1564-67), Civitates Orbis Terrarum (1572), Beckman (1661) Carter (1772-1777), Swinburne (1775-1806), Laborde (1812), Roberts (1833-38), Vivian (1834-39), Dauzats (1835), Chapuy (1842-44), Tenison (1850-53), Vallejo (c. 1850), Schöpel & Poyatos (1850), Guesdon (1853), Deroy (1850-1862). To interpret this graphic set for the first time, their points of view have been located at ten viewpoints, assessing their current status and visual interest. It has been found that the city of Malaga has been drawn from all directions and different distances to the urban centre. This is due to the fact that this territory forms a closed visual basin, delimited by a mountain barrier open to the sea from the South, with several hills of lower altitude and Mount Gibralfaro as a visual reference. In this way, a graphic approach is offered to a city with a complex topography and a rich network of crossed visual relationships reflected in historical images. Some viewpoints of Malaga have disappeared or have been transformed, but the whole constitutes valuable heritage that will allow future generations to continue enjoying unique views of the city and its landscape.
Keywords: Arquitectura - Dibujos y planos; Málaga - En el arte; Málaga - Dibujos y planos; Expresión gráfica arquitectónica; Paisaje; Dibujo